PISA 2015 results. Volume 1, Excellence and equity in education - Organisation for Economic Co-operation and Development (Programme for International Student Assessment, ISSN 1990-8539, 2016)
Summary.
Keywords: koulutus; koulutus : arviointi; opiskelijat : arviointi; kansainvälinen vertailu; matematiikka; lukutaito; luonnontieteet; yhdenvertaisuus; PISA-tutkimus